A case study of construction dispute – case A & B - Ong, Simon Yeow Kuan. (2013)
Before the introduction of the Security of Payments (“SOP”) Act, dispute resolution in the construction industry was a long drawn and costly process. Having no guidelines to follow, legal firms could not resolve the issues effectively, resulting in large expenses.